An informal Facebook Group for English language Interaction: A study of Malaysian university students' perspectives, experiences and behaviours - Kasuma, Shaidatul Akma Adi; Wray, David (2015)
The fundamental design of social networking sites (SNSs) to ease social interactions has generally been viewed as valuable in second language learning. This study set out to examine Malaysian university students' perceptions, experiences and behaviours when presented with an informal English language interaction group on Facebook. Three methods of data collection were employed in stages: an initial questionnaire, the postings on a Facebook interaction group, and subsequent semistructured interviews. The findings show a discrepancy between the students' perceptions and behaviours when they used Facebook for English language learning (ELL) and interaction. While a majority of the participants expressed high interest in using Facebook for ELL, in the actual group they generally acted very passively and did not contribute to any content development. The reasons cited for this behaviour were that the group did not support their needs for ELL, they were too occupied with university work, and simply wanted to act as silent readers. The main type of posts shared by the group members were of a socioacademic nature such as advertisements for university-related events. The interaction threads in the group indicated the participants' interest in three topics; entertainment-based discussions, grammar quizzes and university-related inquiries. The passive members of the group reported small improvements in their English language skills from the interaction activity. On the contrary, the few active participants experienced a boost in their self-confidence to employ English language in a public space, but no improvement in their language skills. The students' experiences and behaviours in the LMT100 group are discussed from three levels of sociocultural influences; personal, societal and institutional. Their familiarity with the face-to-face teachercentred classroom learning that privileged examinations might have hindered their active participation in the Facebook group. Due to the unsuccessful implementation of the informal English language interaction group on Facebook, several strategies that could improve students' participations when Facebook is used for ELL, are presented as implications.